Christianity and digital culture : analysis of users' experiences of the christian social networking site in Taiwan - Walei - Lee, Chia-Ying (2011)
Social Networking Sites (SNSs) have been a popular phenomenon worldwide, while religion in Computer Mediated Communication (CMC) studies has gained more academic attention. Walei as a pioneering social networking site is founded by a group of Protestant Christians targeting at the youth in Taiwan, and it exemplifies religious application on the Internet. This thesis investigates what role such a website plays both for its users and against its competition, particularly in the non-Christian cultural context. Using online interviews with nine users of Walei, how the interactivity affects Christian users‟ religious identity and the impression of non-Christian users toward Christianity is explored. This thesis seeks to shed the light on the interrelation of technology and religion, and the possible influence on identity formation online.